2010
DOI: 10.1186/1477-7827-8-20
|View full text |Cite
|
Sign up to set email alerts
|

Doxorubicin-induced ovarian toxicity

Abstract: BackgroundYoung cancer patients may occasionally face infertility and premature gonadal failure. Apart from its direct effect on follicles and oocytes, chemotherapy may induce ovarian toxicity via an impact on the entire ovary. The role of doxorubicin in potential ovarian failure remains obscure. Our intention was to elucidate doxorubicin-related toxicity within ovaries.MethodsFemale mice were injected intraperitoneally with 7.5 or 10 mg/kg doxorubicin and their ovaries were visualized in vivo by high resoluti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
101
1
5

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 135 publications
(119 citation statements)
references
References 29 publications
12
101
1
5
Order By: Relevance
“…Mice were re-weighed and sacrificed 1 (7, 10, 9 and 15 mice respectively), 3 (8, 10, 10 and 12 mice respectively) or 6 months later (6,8,7 and 8 mice respectively). DXR chosen dose was similar to the dose used in our female gonadal toxicity study (Ben-Aharon et al 2010). DEX chosen dose was calculated according to the dose used in humans (USFDA 2005).…”
Section: Drugs Administration and Experimental Designmentioning
confidence: 99%
“…Mice were re-weighed and sacrificed 1 (7, 10, 9 and 15 mice respectively), 3 (8, 10, 10 and 12 mice respectively) or 6 months later (6,8,7 and 8 mice respectively). DXR chosen dose was similar to the dose used in our female gonadal toxicity study (Ben-Aharon et al 2010). DEX chosen dose was calculated according to the dose used in humans (USFDA 2005).…”
Section: Drugs Administration and Experimental Designmentioning
confidence: 99%
“…More studies are therefore needed to discern the mechanism of action of both drugs. Recent studies have revealed that DXR induces ovarian toxicity, which was observed by a reduction in the ovulation rate and the size of the ovary (OKTEM; OKTAY, 2007;BEN-AHARON et al, 2010). DXR elicits apoptosis by various mechanisms in a variety of cells.…”
Section: Resultsmentioning
confidence: 99%
“…Doxorubicin (DXR) is one of the most commonly used drug (OKTEM;OKTAY, 2007) in the treatment of cancers of bladder, breast, lung, ovary, and other organs (CHOW et al, 2010); this drug transgresses the cell membrane and accumulates in both the nucleus mitochondria by inducing oxidative stress and chromosomal obliteration through the inhibition of topoisomerase II (MAILER;PETIRING, 1976). However, DXR induces ovarian toxicity by reducing the ovulation rate along with reducing the size of the ovary among other side effects (OKTEM;OKTAY, 2007;BEN-AHARON et al, 2010). The poor specificity of these drugs against tumor tissue highlights the need for developing new drugs with fewer side effects (OKTEM; OKTAY, 2007) and more specificity.…”
Section: Introductionmentioning
confidence: 99%
“…This is why in our laboratory, we will repeat the injections of cyclophosphamide in new experiments to try to observe apoptosis in mice ovaries. The studies of Meirow et al Meirow et al (2007) and Aharon Ben-Aharon et al (2010) hypothesized a combined mechanism of neovascularization and ovarian tissue scarring with a direct toxic effect on the primordial follicles. Personally, we think that additional processes that lead to ovarian damage and follicles loss after chemotherapy may be involved such as vascular complications and ischemic mechanisms.…”
Section: Mechanisms Of Ovarian Injurymentioning
confidence: 99%
“…These modes of injury were present in non-atrophic ovaries of patients that were not sterilized by chemotherapy. Ben Aharon and his coworkers Ben-Aharon et al (2010) evaluated the effects of doxocuribin (injected intraperitoneally) on mice ovaries. A single injection of doxorubicin resulted in a major reduction in both ovarian size and weight that lasted even one month post-treatment.…”
Section: Mechanisms Of Ovarian Injurymentioning
confidence: 99%